"Don't Forget that Others Are Watching, Too!" The Effect of Conversational Human Voice and Reply Length on Observers' Perceptions of Complaint Handling in Social Media. Issue 1 (May 2020) - Javornik, Ana; Filieri, Raffaele; Gumann, Ralph
When dissatisfied customers voice their complaints on companies' social media pages, many other consumers can observe such interactions. Yet, only limited research has investigated how complaint handling is perceived by this online audience. Since the final outcome of the complaint is rarely visible publicly, the message characteristics (e.g., length and style) of company replies can represent signaling cues for observers of how the complaint is handled. The results of two experimental studies show that the use of conversational human voice (CHV) leads to more positive observer perceptions of complaint handling as opposed to when a corporate voice is employed. We found that interactional justice fully mediates this process and that satisfaction with complaint handling positively impacts corporate image and indirectly observers' WOM intentions. Surprisingly, high CHV can negatively affect procedural justice, but these effects are mainly offset through interactional justice, as the observers focus on the fairness in the communication exchange. Interestingly, our findings show that, in the case of low CHV, other cues such as the length of the company's reply significantly change perceived justice dimensions; however, the length of reply does not lead to such changes when high CHV is employed. Our studies bring novel findings that contribute to justice and signaling theories in the context of complaints management in social media. Managerial implications are discussed.